Femoral nerve catheter vs local infiltration for analgesia in fast track total knee arthroplasty: short-term and long-term outcomes - Fenten, M.G.E.; Bakker, S.M.K.; Scheffer, G.J.; Wymenga, A.B.; Stienstra, R.; Heesterbeek, P.J.C. (British journal of anaesthesia : BJA, 2018)
The aim was to compare the effects on short-term and long-term pain and functional outcome of periarticular local anaesthetic infiltration (LIA) with LIA of the posterior knee capsule in combination with a femoral nerve block (FNB) catheter in patients undergoing total knee arthroplasty. Eighty patients were randomised to one of two groups: Subjects in group LIA received periarticular LIA with ropivacaine 0.2% for postoperative analgesia; subjects in group FNB received LIA of the posterior capsule and a FNB catheter. The primary outcome parameter was functional capacity of the knee 12 months after surgery. Secondary parameters included mobility as determined by accelerometer data, pain, satisfaction with the analgesic regimen, hospital length of stay, and use of pain medication 3 and 12 months after surgery. There were no differences between groups in long-term functional capacity, patient satisfaction and hospital length of stay. In the first 2 days, subjects in group FNB had slightly lower pain scores and used less opioids, and subjects in group LIA had a higher level of accelerometer activity. Three and 12 months after surgery, subjects in group FNB had lower maximum pain scores and were less likely to use any pain medication 12 months after surgery. Both techniques were similar regarding long-term functional outcome. Subjects in group FNB had slightly lower pain scores and lower opioid consumption after operation, lower maximum pain scores at 3 and 12 months, and were less likely to use any pain medication at 12 months. NCT01966263.